2018
DOI: 10.1111/cas.13539
|View full text |Cite
|
Sign up to set email alerts
|

KIAA0247 inhibits growth, migration, invasion of non‐small‐cell lung cancer through regulating the Notch pathway

Abstract: Lung cancer remains the leading cause of cancer‐related death worldwide. Previous studies have shown that the novel KIAA0247 gene potentially targeted by the tumor suppressor p53 may inhibit the development of several cancers. However, the exact function of KIAA0247 in non‐small‐cell lung cancer (NSCLC) is unknown. The purpose of the present study was to clarify the role of KIAA0247 in NSCLC. KIAA0247 expression was evaluated in tumors and adjacent normal tissues of 197 NSCLC patients by immunohistochemistry a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 32 publications
(46 reference statements)
1
20
0
Order By: Relevance
“…Licciulli et al[30] found that NOTCH1 function was required for the initiation of lung adenocarcinoma, belonging to the histopathologic class of NSCLC, and controlled tumor cell survival via suppression of p53-mediated apoptosis through the regulation of p53 stability. Recent study by Xu et al showed that KIAA0247 restrained NSCLC progression through attenuating proliferation, migration and invasion of cancer cells through inhibition of the NOTCH pathway[31]. Clinically oriented studies have highlighted that NOTCH signaling impacts survival in lung cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Licciulli et al[30] found that NOTCH1 function was required for the initiation of lung adenocarcinoma, belonging to the histopathologic class of NSCLC, and controlled tumor cell survival via suppression of p53-mediated apoptosis through the regulation of p53 stability. Recent study by Xu et al showed that KIAA0247 restrained NSCLC progression through attenuating proliferation, migration and invasion of cancer cells through inhibition of the NOTCH pathway[31]. Clinically oriented studies have highlighted that NOTCH signaling impacts survival in lung cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…HBE cells were cultured in Dulbecco’s modified Eagle medium (DMEM) with high glucose; A549, H1299, H460, H226, and H292 cells were cultured in Roswell Park Memorial Institute 1640 medium; and SK-MES-1 cells were cultured in MEM medium. Cells were maintained in a 5% CO 2 incubator at 37°C [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…A wound was scratched using a 100-μl pipette tip. The gap was photographed at 0 h and 24 h [16]. The invasion of Caki-2 cells was detected using a BioCoat™ Matrigel-coated Invasion Chamber (8.0-μm membrane, BD Biosciences, USA).…”
Section: Methodsmentioning
confidence: 99%